Filling the data gap on CGRP mAb therapy in low- to middle-income countries in Southeast Asia: insights from a real-world study in Thailand - Prakit Anukoolwittaya; Akarin Hiransuthikul; Thanakit Pongpitakmetha; Sekh Thanprasertsuk; Wanakorn Rattanawong (My University, 2024)
Most real-world data on CGRP mAbs have been published from high-income countries such as the USA, Western countries, Japan, Korea, and Singapore. However, data from low- and middle-income countries in Southeast Asia is lacking. This is the first real-world study from Thailand to describe the efficacy of CGRP mAbs therapy in migraine patients and to analyze the response trends between episodic migraine and chronic migraine.
Keywords: Migraine and Headache Studies